PENGARUH STRUKTUR MODAL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2015 SAMPAI DENGAN 2019 - Rohana, Siti; Makhdalena, Makhdalena; Syahza, lmasdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose ofthis research is to examine and analyze the effect of capital structure on dividend policy. The population of this study are companies listed on the Indonesia Stock Exchange which have complete data on the Debt Equity Ratio and Dividend Payout Ratio for 5consecutive years (2015-2019). This type of research variable data is secondary data obtained by documentation techniques sourced from ICMD. Methods of data analysis using regression. The result of research that have been carried out show that capital structure has a significant effect on dividend policy.Key Words: Capital Structure, Debt Equity Ratio (DER), Dividend Policy, Dividen Payout Ratio (DPR).